2016
DOI: 10.1155/2016/2539781
|View full text |Cite
|
Sign up to set email alerts
|

The New Role of CD163 in the Differentiation of Bone Marrow Stromal Cells into Vascular Endothelial‐Like Cells

Abstract: Bone marrow stromal cells (BMSCs) can differentiate into vascular endothelial cells (VECs). It is regarded as an important solution to cure many diseases, such as ischemic diseases and diabetes. However, the mechanisms underlying BMSC differentiation into VECs are not well understood. Recent reports showed that CD163 expression was associated with angiogenesis. In this study, overexpression of CD163 in BMSCs elevated the protein level of the endothelial-associated markers CD31, Flk-1, eNOS, and VE-cadherin, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…51 Disappointingly, these agents have not been successful in trials, which may be because increased levels of TAMs may still be present after anti-angiogenesis therapies; the number of CD163+ TAMs significantly correlated with an overall decreased survival among patients with recurrent GBM. 14 Recently, Wei Lu 52 demonstrated that overexpressed CD163 in bone marrow stromal cells (BMSCs) elevated protein levels of endothelial-associated markers such as CD31, Flk-1, eNOS, and VE-cadherin, significantly promoting angiogenesis. They also found that CD163 was involved in Hmbox1/CD163/FGF-2 signal pathway in BMSC differentiation into vascular endothelial-like cells, which suggested that CD163 was a key regulator in angiogenesis and provided a novel target for further investigating the gene control of BMSC differentiation into vascular endothelial-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…51 Disappointingly, these agents have not been successful in trials, which may be because increased levels of TAMs may still be present after anti-angiogenesis therapies; the number of CD163+ TAMs significantly correlated with an overall decreased survival among patients with recurrent GBM. 14 Recently, Wei Lu 52 demonstrated that overexpressed CD163 in bone marrow stromal cells (BMSCs) elevated protein levels of endothelial-associated markers such as CD31, Flk-1, eNOS, and VE-cadherin, significantly promoting angiogenesis. They also found that CD163 was involved in Hmbox1/CD163/FGF-2 signal pathway in BMSC differentiation into vascular endothelial-like cells, which suggested that CD163 was a key regulator in angiogenesis and provided a novel target for further investigating the gene control of BMSC differentiation into vascular endothelial-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 CD163 is also a marker of alternatively activated anti-inflammatory macrophages/microglia that are abundant during the resolution phase of the inflammatory process, and has been postulated to participate in angiogenic repair mechanisms. [10][11][12] It is of considerable interest that no studies have evaluated the role of CD163 after ICH, given its aforementioned functions and reports using human autopsy specimens and a porcine model demonstrating that CD163-positive macrophages/microglia accumulate in the brain following ICH. [13][14][15] Using CD163-deficient mice, we reveal that CD163 has distinct temporal influences on ICH outcomes, with early deleterious properties and delayed beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been reported to be able to differentiate into VSMC-like or EC-like cells with the stimulation of TGFβ1 or VEGF, respectively. Moreover, it is well recognized that angiogenesis is regulated by mechanobiological factors, such as substrate stiffness and geometrical confinements . Increasing evidence has demonstrated that tissue stiffness and mechanical stimuli are the key cellular microenvironment.…”
Section: Results and Discussionmentioning
confidence: 99%